Global engagement : cooperation and security in the 21st century - Nolan, Janne E. (Washington, D.C. : Brookings Institution, 1994)
Worldwide political changes have presented a unique opportunity for forging a new basis of international security relations. The end of the cold war, the dissolution of the Soviet Union, and the ascending role of the United Nations in regional security affairs have transformed the driving issues of international security. These changes both heighten the demand and offer the potential for global cooperation on an unprecedented scale. Traditional security preoccupations and the foundations of past strategy--based on preparation for massive military confrontation--are no longer appropriate. Now w.
E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z
Includes bibliographical references and index.
JSTOR
Keywords: Nuclear disarmament; Security, International; International cooperation; Désarmement nucléaire.; Coopération internationale; International cooperation; Nuclear disarmament; Security, International; POLITICAL SCIENCE / Security (National & International)